CRIME OF MAKAR AND ITS ENFORCEMENT IN POST-REFORM INDONESIA - Sulaeman, Eman (Walisongo Law Review (Walrev), 2019)
In the era of reforms characterized by freedom of thought and opinion, the position of makar crime formulation in the criminal law book (KUHP) is very dilemmatic. Its  Formulation is needed to maintain state sovereignty. However,  its presence has not well defined yet. So,  it threatens the independence of Makar crime and its elements. This research will analyze the formulation of Makar crime in the Criminal law book (KUHP), its enforcement in Indonesia post-reforms, and its draft formulation in the Criminal law book (KUHP). Library research method through juridical-normative was used in this research. The result shows that the formulation of Makar crime which was set forth in Article 104, 106, 107, and 108 of the Criminal law book (KUHP) still has not define Makar and its parameters to the elements. Therefore, it is necessary to reform the criminal law effectively in accordance with the principles of law and democratic state in the Draft Law (RUU) of the Criminal law book (KUHP) in order to overcome makar crime.